Environmental, health, wellbeing, social and equity effects of urban green space interventions: A meta-narrative evidence synthesis. (September 2019) - Hunter, R.F.; Cleland, C.; Cleary, A.; Droomers, M.; Wheeler, B.W.; Sinnett, D.; Nieuwenhuijsen, M.J.; Braubach, M.
Abstract: Background: As populations become increasingly urbanised, the preservation of urban green space (UGS) becomes paramount. UGS is not just dedicated recreational space such as public parks, but other types of informal green space are important, for example, street trees and roof gardens. Despite the potential from cross-sectional evidence, we know little about how to design new, or improve or promote existing UGS for health, wellbeing, social and environmental benefits, or known influencing factors such as physical activity. Objectives: To perform a meta-narrative review of the evidence regarding the health, wellbeing, social, environmental and equity effects, or known influencing factors of these outcomes, of UGS interventions. Data sources: Eight electronic databases were searched ((Medline, PsycINFO, Web of Science (Science and Social Science Citation Indices), PADDI (Planning Architecture Design Database Ireland), Zetoc, Scopus, Greenfiles, SIGLE (System for Information on Grey Literature in Europe)), and reference lists of included studies and relevant reviews were hand searched for further relevant studies. Study eligibility criteria, participants, and interventions: Eligibility criteria included: (i) evaluation of an UGS intervention; and (ii) health, wellbeing, social or environmental outcome(s), or known influencing factors of these outcomes, measured. Interventions involving any age group were included. Interventions must have involved: (a) physical change to green space in an urban-context including improvements to existing UGS or development of new UGS, or (b) combination of physical change to UGS supplemented by a specific UGS awareness, marketing or promotion programme to encourage use of UGS. Study appraisal and synthesis methods: Following a meta-narrative approach, evidence was synthesised by main intervention approach, including: (i) park-based; (ii) greenways/trails; (iii) urban greening; (iv) large green built projects for environmental purposes. Outcomes such as economic (e.g. cost effectiveness and cost–benefit analyses), adverse effects and unintended consequences were also extracted. Evidence was synthesised following the RAMESES guidelines and publication standards, the PROGRESS-plus tool was used to explore equity impact, and risk of bias/study quality was assessed. The findings from the evidence review were presented at an expert panel representing various disciplines in a workshop and these discussions framed the findings of the review and provide recommendations that are relevant to policy, practice and research. Results: Of the 6997 studies identified, 38 were included. There was strong evidence to support park-based (7/7 studies) and greenway/trail (3/3 studies) interventions employing a dual-approach (i.e. a physical change to the UGS and promotion/marketing programmes) particularly for park use and physical activity; strong evidence for the greening of vacant lots (4/4 studies) for health, wellbeing (e.g. reduction in stress) and social (e.g. reduction in crime, increased perceptions of safety) outcomes; strong evidence for the provision of urban street trees (3/4 studies) and green built interventions for storm water management (6/7 studies) for environmental outcomes (e.g. increased biodiversity, reduction in illegal dumping). Park-based or greenway/trail interventions that did not employ a dual-approach were largely ineffective (7/12 studies showed no significant intervention effect). Overall, the included studies have inherent biases owing to the largely non-randomized study designs employed. There was too little evidence to draw firm conclusions regarding the impact of UGS interventions on a range of equity indicators. Limitations; conclusions and implications of key findings: UGS has an important role to play in creating a culture of health and wellbeing. Results from this study provide supportive evidence regarding the use of certain UGS interventions for health, social and environmental benefits. These findings should be interpreted in light of the heterogeneous nature of the evidence base, including diverging methods, target populations, settings and outcomes. We could draw little conclusions regarding the equity impact of UGS interventions. However, the true potential of UGS has not been realised as studies have typically under-evaluated UGS interventions by not taking account of the multifunctional nature of UGS. The findings have implications for policymakers, practitioners and researchers. For example, for policymakers the trajectory of evidence is generally towards a positive association between UGS and health, wellbeing, social and environmental outcomes, but any intervention must ensure that negative consequences of gentrification and unequal access are minimised. Highlights: As populations become increasingly urbanised, the preservation of UGS is paramount. We found supportive evidence for certain UGS interventions for health, social and environment. Interventions employing a dual approach were particularly effective. Intervention must ensure that negative consequences are minimised.